2021
DOI: 10.3390/electronics10202554
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Grained Implicit Sentiment in Financial News: Uncovering Hidden Bulls and Bears

Abstract: The field of sentiment analysis is currently dominated by the detection of attitudes in lexically explicit texts such as user reviews and social media posts. In objective text genres such as economic news, indirect expressions of sentiment are common. Here, a positive or negative attitude toward an entity must be inferred from connotational or real-world knowledge. To capture all expressions of subjectivity, a need exists for fine-grained resources and approaches for implicit sentiment analysis. We present the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…Sentiment analysis methods can be categorized into: corpus-based methods and deep learning-based methods. In terms of implicit corpus-based approaches, Jacobs et al 9 constructed an implicit SENTiVENT corpus of English business news and conducted coarse-grained implicit sentiment analysis experiments on this dataset, and found that the existing explicit sentiment models could not be directly applied in implicit sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Sentiment analysis methods can be categorized into: corpus-based methods and deep learning-based methods. In terms of implicit corpus-based approaches, Jacobs et al 9 constructed an implicit SENTiVENT corpus of English business news and conducted coarse-grained implicit sentiment analysis experiments on this dataset, and found that the existing explicit sentiment models could not be directly applied in implicit sentiment analysis.…”
Section: Related Workmentioning
confidence: 99%
“…It is highlighted that the user's bearish tendencies implied a higher market volatility and reflect a possible higher market return. Moreover, there is a SENTiVENT corpus presented by [65] consisting of the token-level annotations for target spans, polar spans and polarity, and training the model based on corresponding annotations for stock movement prediction.…”
Section: Sentiment-based Stock Forecasting Approachmentioning
confidence: 99%
“…In order to make these separate works in practical use for the complete ABSA task, one typical way is to pipeline these two sub-tasks together to a relatively integrated method [6,7,9,[16][17][18][19]39].…”
Section: Pipeline Approachesmentioning
confidence: 99%
“…As the dominant line of research in fine-grained opinion mining, aspect-based sentiment analysis (ABSA) aims to identify sentiment of target entities and their aspects. Specifically, given a target entity of interest, ABSA methods can extract its properties and identify the sentiment expressed about those properties [6]. From a technological point of view, the methodologies can be divided into two sub-tasks, namely opinion target extraction and target sentiment identification [4,5], which corresponds to the above-mentioned interested target entity properties extraction and expresses sentiment identification.…”
Section: Introductionmentioning
confidence: 99%